2016
DOI: 10.21037/qims.2016.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic clues for diagnosis of spina bifida occulta in children

Abstract: Background:The aim of the current study was to find out if spinal ultrasonography might have a predictive potential for detection of spina bifida occulta (SBO) in pediatric nocturnal enuresis patients.Methods: A total of 108 children (58 females, 50 males) with a mean age of 8 (range, 6-15) years diagnosed for nocturnal enuresis in our tertiary care center were included in this cross-sectional analysis. Half of the cases (n=54, 50%) were found to have SBO, while the other half did not have SBO. After obtaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Also, evaluation of post void residue by ultrasonography was used in these children to diagnose lower urinary dysfunction (22). Ultrasonography had also been used in diagnosis of spina bifida occulta in children with nocturnal enuresis and can be useful in evaluating the treatment of these children (14,23). The aim of the current study was to determine the frequency of urinary tract abnormalities found in ultrasound of children with MPNE and to compare with children without MPNE to determine whether or not to performing ultrasound in these children is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, evaluation of post void residue by ultrasonography was used in these children to diagnose lower urinary dysfunction (22). Ultrasonography had also been used in diagnosis of spina bifida occulta in children with nocturnal enuresis and can be useful in evaluating the treatment of these children (14,23). The aim of the current study was to determine the frequency of urinary tract abnormalities found in ultrasound of children with MPNE and to compare with children without MPNE to determine whether or not to performing ultrasound in these children is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to use ultrasound in the diagnosis of spina bifida occulta (SBO) in children with enuresis. The sign of "single and double echogeneous cap signs and the V-shaped tip of spine" in the L5 and S1 can be useful in detecting SBO (14).…”
Section: Introductionmentioning
confidence: 99%
“…Plain radiographs of the spine performed as the primary imaging modality (where dysraphy was not always found). All patients underwent magnetic resonance imaging, while in 7cases computed tomography (CT) was performed to further assess bone deformities (16)(17)(18)(19) Magnetic resonance imaging showed the pathology, congenital anatomical abnormality and the tract in all cases Figure3. The surgery aimed to excise the sinus tract completely, excisable skin tags, and correct the dysraphic state in the same setting (2,20,21) Surgical steps were common for all the cases.…”
Section: Discussionmentioning
confidence: 99%
“…US is the first-line imaging technique for the assessment of the spine and its content in the youngest children [296][297][298][299][300][301][302][303][304]. During the first 3-6 months of life, the incompletely ossified posterior vertebral arch offers a valuable acoustic window to spinal US.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…However, MRI remains the first-line technique in older children when ossification of the posterior arch is complete [306]. Newborns should undergo spinal US evaluation in the following circumstances: posterior midline cutaneous markers (midline or paramedian back masses or dimples higher than the intergluteal fold especially when associated with midline skin discoloration, skin tags, hair tufts, hemangiomas), foot abnormalities, anorectal and genitourinary malformations and neurologically abnormal lower limbs, spina bifida occulta, tethered cord, intracanal masses, raphe dysraphism including myelomeningocele, myeloceles [296][297][298][299][300][301][302][303][304]. Nevertheless, the diagnosis should ultimately be confirmed and characterized by MRI.…”
Section: Clinical Applicationsmentioning
confidence: 99%